2017
DOI: 10.1186/s12966-017-0481-3
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary patterns, physical activity and health-related physical fitness in youth: a cross-sectional study

Abstract: BackgroundStrong evidence indicates that moderate-vigorous physical activity (MVPA) is positively associated with fitness in youth, independent of total sedentary-time. Sedentary-time appears negatively associated with fitness only when it replaces MVPA. However, whether different sedentary-patterns affect health-related fitness is unknown.MethodsThe associations between MVPA and sedentary-patterns with physical fitness were examined in 2698 youths (1262 boys) aged 13.4 ± 2.28 years. Sedentary-time (counts · m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
101
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(116 citation statements)
references
References 45 publications
6
101
1
8
Order By: Relevance
“…The excessive daily time in sedentary activities in the students of the present study is at least similar to those observed in adolescents from developed countries 5,9,23 . Direct comparisons between the studies regarding the Breaks (breaks/hour) 11.3 ± 2.5 11.7 ± 2.4 11.6 ± 2.3 11.5 ± 2.5 11.6 ± 2.5 *p < 0.05. .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The excessive daily time in sedentary activities in the students of the present study is at least similar to those observed in adolescents from developed countries 5,9,23 . Direct comparisons between the studies regarding the Breaks (breaks/hour) 11.3 ± 2.5 11.7 ± 2.4 11.6 ± 2.3 11.5 ± 2.5 11.6 ± 2.5 *p < 0.05. .…”
Section: Discussionsupporting
confidence: 85%
“…More recently, the pattern of sedentary behavior, that is, how this behavior is accumulated (volume) throughout the day or week in terms of series (bouts) and interruptions (breaks) 3 has been the object of research, given its probable relationship with health outcomes in young people [4][5][6] . Although there is still limited evidence to support this relationship 7 , recommendations on sedentary behavior for young people already include the need to interrupt prolonged periods of sitting as often as possible 8 .Thus, quantification of the pattern of sedentary behavior in children and adolescents allows better understanding of how this behavior manifests in this population group, assisting future interventionist strategies, as well as enabling monitoring of trends.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of physical activity among adolescents is common worldwide; less than 20% of them engage in the recommended amount of physical activity (World Health Organization, ). Along with insufficient physical activity, poor eating habit is the leading cause of obesity and other noncommunicable diseases in later life (Bouchard, Blair, & Katzmarzyk, ; Judice et al, ). High body mass index (BMI), low physical activity, and poor eating habits are not only strong predictors of metabolic disease but also modifiable risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Young people with greater adiposity perceive themselves as having less energy likely due to the greater effort required to perform physical activities. conversely, those who are more active present greater cardiorespiratory fitness and functional capacity compared to young people with low fitness [24] and therefore have greater vigor for physical exertion.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the cross-sectional design adopted, some information may explain the results found in the present study. Young people with higher adiposity and lower cardiorespiratory fitness presented lower HrQOL scores in the physical well-being dimension probably due to the inverse association between physical activity and adiposity [23] and the positive association between physical activity and cardiorespiratory fitness [24]. In addition, the physical well-being dimension assesses whether the young people have a lot of energy and perceive themselves to be in good shape.…”
Section: Discussionmentioning
confidence: 99%